2013
DOI: 10.1088/0951-7715/26/3/763
|View full text |Cite
|
Sign up to set email alerts
|

On non-regularg-measures

Abstract: Abstract. We prove that g-functions whose set of discontinuity points has strictly negative topological pressure and which satisfy an assumption that is weaker than non-nullness, have at least one stationary g-measure. We also obtain uniqueness by adding conditions on the set of continuity points.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 16 publications
(33 reference statements)
0
40
0
Order By: Relevance
“…For instance, Comets et al [20] have shown that, if a inf w p(a|w) ≥ δ and ct(k) ≤ C k −(1+α) for constants C, α, δ > 0, then the process X is φ-mixing with polynomial rate ≈ k −α . On the other hand, there seem to be no known examples of processes that are not a.s. continuous [17], so "ct(X −1 −k ) → 0 almost surely" (and non-uniformly) is compatible with many different kinds of mixing hypotheses.…”
Section: Remark 2 (Relationship To Continuity and Mixing Properties):mentioning
confidence: 81%
“…For instance, Comets et al [20] have shown that, if a inf w p(a|w) ≥ δ and ct(k) ≤ C k −(1+α) for constants C, α, δ > 0, then the process X is φ-mixing with polynomial rate ≈ k −α . On the other hand, there seem to be no known examples of processes that are not a.s. continuous [17], so "ct(X −1 −k ) → 0 almost surely" (and non-uniformly) is compatible with many different kinds of mixing hypotheses.…”
Section: Remark 2 (Relationship To Continuity and Mixing Properties):mentioning
confidence: 81%
“…s A(α) * E A(α)A s ) = Tr(A(α) * E A(α)I) = ν(α),so ν is consistent with extensions to the left. Similarly,(3) shows that s ν(αs) = ν(α).…”
mentioning
confidence: 84%
“…They constitute an important class of stochastic models, which includes, for example, Markov chains, stochastic models that exhibit nonuniqueness and models that are not Gibbsian (Fernández et al, 2011). The question of uniqueness of g-measures was extensively studied and important progresses have been obtained in several areas related to probability and ergodic theory, from the seminal works of Onicescu & Mihoc (1935); Doeblin & Fortet (1937) to recent advances in Johansson et al (2012); Gallo & Paccaut (2013), and the contributions of Harris (1955); Keane (1972); Walters (1975); Lalley (1986); Stenflo (2003); Fernández & Maillard (2005) among many others. Notwithstanding, the problem of non-uniqueness is much less understood and the literature is still based on few examples (Bramson & Kalikow, 1993;Hulse, 2006;Berger et al, 2005).…”
Section: Introductionmentioning
confidence: 99%